Analisa Manajemen Dan Efisiensi Penyediaam Pakan Ayam Pada Poultry Shop - R. Syafriardi; Fitrini Fitrini; Kamaruzzaman Kamaruzzaman (Universitas Andalas, 2006)
The objectives of this research were to determine the optimum quantity of feed stocked or ordered which gave the most economic efficiency in daily management practices of poultry- shop. The case study was conducted at Rajawali poultry shop, located in Lubuk Begalung sub district, Padang city. Data or information collected included: kind of feed stocked; volume and time schedule of feed ordered; procedures and cost of feed ordering, handling, storage and distribution. The data were statistically analyzed by using Economic Order Quantity Method. The results showed that the poultry shop was applied good stock management practices. The quantity and frequency of feed ordered of 69,784 kg for every 2 days was found the most optimum management practices which might save cost of about Rp. 9,064,874 for the year of 2006.